Description of a new species of cusk-eel (Teleostei, Ophidiiformes, Ophidiidae, Ophidion) from the Galápagos Archipelago and Isla del Coco, long known but previously undescribed - Lea, Robert N.; Robins, C. Richard (Zootaxa, 2024)
A cusk-eel, known from the Galápagos Archipelago since 1905, which has remained undescribed, is herein formally named, Ophidion galapagensis Lea & Robins. The species is known from 10 collections, including material from Isla del Coco. The species is endemic to the Galápagos Archipelago–Isla del Cocos biogeographic complex and is compared to the seven known eastern Pacific ophidiine cusk-eels; its relationship to these species is unclear. It is distinguished by dorsal-fin ray, anal-fin ray, and vertebral counts, and the relationship of pelvic-fin filaments and pectoral-fin length. It is most frequently collected by ichthyocide from depths between 3–25 m and taken by bottom trawl to depths of 110 m. It is occasionally observed by scuba divers during night dives.